Analisis Makespan Job shop Menggunakan Metode Active, Non-Delay dan Heuristic Generation - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This paper reports a proposed solution to the problem that commonly exists in the Job Shop industry which apply MOT system with varying type of repetitive product. Three algorithm scheduling methods have been used to look at a make span during production process i.e. Active Generation (AG), Non Delay Generation (NDG) and Heuristic Generation (HG). Seven types of product have been applied as research subject: Ring, Bushing, Coupling head, Pin-I, Pull shaft-2, Split Cam nller and Bush. The results show that among those methods, AG and NDG methods gave the make span drop up to 46.03 %, while HG method reduced its make span up to 36.35 %.